Factors Influencing Young Women’s Self Concept In Facing Primary Dysmenorrhoea At Smp Negeri 8 Medan - Faradita Wahyuni (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Preliminary study of 2018 in Ponorogo, about the effect of menstrual pain on daily activities, there were 11 people from 49 respondents or as much as 22,4% admitted his activity was disrupted due to menstrual pain and 3 people from 49 respondents or as much as 6,2% said experiencing pain weight during menstruation, Of the case studies are suspected that the concept of self plays a major role for adolescents in dealing with dysmenorrhea during menarche. This research use analytic research design with cross sectional approach. Sample taken by random sampling. The result showed that there is a significant influence between the independent variables of development, significant-other, self-perseptions studied with the dependent variable self-concept where optained R Value of 0,694 and R Square 0,482 which means the independent variable contributes influence on the dependent varible of 48,2%. Based on F test found that the results of the three independent variables strongly influence the dependent variable where obtained P = 0,000<0,05. But based on T test, it is found that the variables that influence only self perception with P = 0,000 < 0,05 whereas developmental variable with sig 0,175 and significant other to sig 0,234 are concidered have no effect to self concept variable. The conclution of this study is the adolescent self-perseption of himself most influential on the formation of adolescent self-concept. Good self-perception will shape good self concept and vice versa.